SAT0315 Demyelinating Syndrome Secondary To Systemic Lupus Erythematosus: Systematic Literature Review and Analysis of A Monocentric Cohort. (15th July 2016) - Piga, M.; Chessa, E.; Floris, A.; Cauli, A.; Mathieu, A.
Abstract : Background: Demyelinating syndrome (DS) secondary to Systemic Lupus Erythematosus (SLE) is rare (<1%) but represents a challenging condition for both patients and clinicians. Objectives: To describe the features of DS secondary to SLE through a systematic review and the analysis of a monocentric cohort of patients. Methods: Using PubMed a systematic review was carried out according to PRISMA guidelines including the following Mesh terms: " Lupus Erythematosus, Systemic", "Lupus Vasculitis, Central Nervous System", "Demyelinating Diseases", "Leukoencephalopathies", "Vasculitis, Central Nervous System", "Cranial Nerve Diseases", "Diplopia", "Brain Stem". Last Medline was performed on the 31/01/2015. Moreover, a retrospective analysis of 334 SLE adult patients, followed-up in a third level center of Rheumatology between 1990 and 2015, was performed to identify those patients that developed DS. Patients were classified as affected with DS defined as acute of relapsing demyelinating encephalomyelitis with evidence of discrete neurologic lesions distributed in space and time according to the 1999 ACR nomenclature and attributed to SLE according to the algorithm proposed by the Italian Society of Rheumatology (1). Cases identified by systematic review and cohort analysis were classified as affected by 4 different syndromes: A) neuromyelitis optica (NMO), B) neuromyelitis optica spectrum disorders (NMOS), C) DS prevalently involving the brain (DSB), D) DS prevalently involving the brainstem (DSBS). Results: The literature search identified 1612 articles, of which 50 were considered relevant for the present study for a total of 74 case reports. The retrospective cohort analysis retrieved 4 cases. Presented data have been pooled. The mean age at the time of DS onset was 33.3 years and only 6 patients were male. DS was the onset manifestation in 57 (73.1%) patients. Among the 78 patients identified 40 (51.3%) were classified as suffering with NMOS, 23 (29.5%) with NMO, 8 (10.2%) with DSBS and 7 with DSB (9.0%). The clinical spectrum of the identified syndromes was heterogeneous but longitudinal extensive transverse myelitis was the most frequent manifestation being present in 23 patients with NMO and 26 (65.0%) with NMOS. Cranial nerve palsies was the less frequent being present in 9 (11.5%) patients (4 NMOS, 3 NMO, 1 DSBS and 1DSB). The most prescribed treatment was methylprednisolone pulses (60, 76.9%) associated with cyclophosphamide (36, 46.1%), but plasma-exchange (15, 19.2%) and Rituximab (7, 9.0%) were also used. Worse functional prognosis was associated with NMO (8.7% complete and 34.8% partial resolution). Demise was reported in 6 NMO cases (26%), 3 (7.5%) NMOS and 1 (14.2) DSB as a results of DS or associated complications. Conclusions: Although rare DS secondary to SLE may be life-threatening. If DS occurs in SLE patients it should be promptly treated with high dose of intravenous corticosteroids and Cyclophosphamide or Rituximab as steroid sparing agents. References: Bortoluzzi A et al. Development and validation of a new algorithm for attribution of neuropsychiatric events in systemic lupus erythematosus. Rheumatology (Oxford). 2015 May;54(5):891–8. Disclosure of Interest: None declared